What do physiotherapists and manual handling advisors consider the safest lifting posture, and do back beliefs influence their choice?. (February 2018) - Nolan, David; O'Sullivan, Kieran; Stephenson, John; O'Sullivan, Peter; Lucock, Michael
Abstract: Background: It is commonly believed lifting is dangerous and the back should be straight during lifting. These beliefs may arise from healthcare professionals, yet no study has evaluated the lifting and back beliefs of manual handling advisors (MHAs) and physiotherapists (PTs). Objectives: To evaluate (i) what lifting technique MHAs and PTs perceive as safest, and why, and (ii) the back pain beliefs of MHAs and PTs. Design: Data was collected via an electronic survey. Method: Participants selected the safest lifting posture from four options: two with a straight back and two with a more rounded back, with justification. Back beliefs were collected via the Back-Pain Attitudes Questionnaire (Back-PAQ). Relationships were investigated using multiple linear and logistic regression models. Results: 400 PTs and MHAs completed the survey. 75% of PTs and 91% of MHAs chose a straight lifting posture as safest, mostly on the basis that it avoided rounding of the back. MHAs scored significantly higher than PTs on the Back-PAQ instrument (mean difference = 33.9), indicating more negative back beliefs. Those who chose the straight back position had significantly more negative back beliefs (mean 81.9, SD 22.7) than those who chose a round back lift (mean 61.7, SD 21.1). Conclusion: Avoiding rounding the back while lifting is a common belief in PTs and MHAs, despite the lack of evidence that any specific spinal posture is a risk factor for low back pain. MHAs, and those who perceived a straight back position as safest, had significantly more negative back beliefs.